STUDI TERMODINAMIKA PENUMBUHAN LAPISAN TIPIS Ga2Te3 - Yanuar Hamzah; Ariswan Ariswan (Universitas Riau, 2022)
Understanding the thermodynamic properties of Ga2Te3 material is a basic concept in material applications. Ga2Te3 material has attracted the attention of many researchers, especially its application in photodetector devices, light-emitting diodes, nano-electronics, and lithium storage materials. Therefore, this research studied the Ga-Te system thermodynamically optimized crystal temperature using F*A*C*T software. The availability of thermodynamic data from this study may be helpful in the experiments. A thin layer of Ga2Te3 fabricates using the closed space vapor transport method. A thin layer of Ga2Te3 characterizes by x-ray diffraction and energy dispersive spectroscopy (EDX). The thin layer of Ga2Te3 resulting from deposition is cubic structured crystalline, and its composition is stoichiometric. The results of the thermodynamic study of the deposit of the thin film Ga2Te3 explain a thorough understanding of the formation mechanism of the reactions that occur in the closed space vapor transport method in the vertical reactor.